Determining Company Strategy Using Balanced Scorecard Framework: Case Study Hakmaz Taba Sharia Hotel - Nugraha, Indra; Mulyono, Nur Budi (Journal of Business and Management, 2017)
AbstractNowadays, hotel is a primary need for travelers and tourist. As a moeslem-majority country, Indonesia at least should be supporting sharia-based hospitality industry. HTS Hotel is a sharia-based hotel which located in Lubuklinggau, South Sumatra. The region itself also have high developtment that attract many tourism. HTS hotel performances must be researched in order to balance the region improvement, and competition. The author will elaborate the factor in the perspective of Balance Scorecard Framework and then generated new strategy that appropiate with condition of HTS Hotel as the final outcomes of this research. The author will assess the performance through questionnaire and interviewing the stakeholder of HTS hotel. In previous years, HTS Hotel management has never been able to achieve the Strategy set. This happens because in the earlier time of the developtment of HTS Hotel the top management using classical method which estimates are based on the personal demand of HTS Hotel top management, while defining KPIs actually should be measured either by the method of the Balanced Scorecard (BSC), which makes the generated strategy is more realistic and can be achieved by the company during the period such as expected.Ã‚Â Keywords: Hotel, KPI, Performance Management, Tourism, Balance Scorecard